Tips and tricks in orthopedic surgery - Damle, Ajit N. (Jaypee Brothers Medical Publishers (P) Ltd., 2015)
Tips & Tricks in Orthopedic Surgery provides comprehensive guidance for identifying and treating orthopaedic injuries. Each of the 46 topics is covered in depth, aiding orthopaedic surgeons, consultants, residents, fellows and postgraduate students in formulating appropriate diagnoses and selecting treatment modalities.